Scalability Aware Energy Consumption and Dissipation Models for Wireless Sensor Networks - Mohamed El Fissaoui; Said Benkirane; Abderrahim Beni-Hssane; Mostafa Saadi (International Journal of Electrical and Computer Engineering (IJECE), 2017)
Most of Wireless Sensor Networks researches focus on reducing the amount of energy consumed by nodes and network to increase the network lifetime. Thus, several papers have been presented and published to optimize energy consumption in each area of WSNs, such as routing, localization, coverage, security, etc. To test and evaluate their propositions, authors apply an energy dissipation model; this model must be more realistic and suitable to give good results. In this paper we present a general preview on different sources of energy consumption in wireless sensor networks, and provide a comparative study between two energy models used in WSNs that offer an effective and an adequate tool for researchers.